Selected aspects of palliative care and quality of life at the terminal stage of neoplastic disease - Farbicka, Paulina; Nowicki, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2012)
Neoplastic diseases are among the most common causes of death. The quality of life in neoplastic disease depends on the type of neoplasm, level of progression, location, treatment possibilities and prognosis. Cancer reduces the quality of life at the advanced stage of disease. At this time patients feel pain and suffering. Palliative care is used in the terminal phase of neoplastic disease. It includes overall care of an incurable patient and her/his family. The main objective of palliative care is meeting somatic and psycho-social requirements. Recently, more and more physicians dealing with oncological patients are moving away from treatment of the patient like an object. They pay attention to a subjective approach to treatment outcomes that are felt by the patient. The model of medicine is becoming a holistic one and during examination physicians pay attention to the patient’s physical and mental state, economic condition, social situation, feelings or lack of complaints more often. Research on quality of life is becoming a vital part of medical examination.